2015
DOI: 10.1017/jfm.2015.349
|View full text |Cite
|
Sign up to set email alerts
|

Performance considerations for expansion tube operation with a shock-heated secondary driver

Abstract: This paper reports on a study examining operation of a shockheated secondary driver across the entire operating envelope of a free-piston driven expansion tube. It is found that the secondary driver operating characteristics depend significantly on the specific characteristics of the flow condition. Key trends and characteristics are identified, and theoretical concepts are validated by numerical analysis and experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…The useful flow interval begins when the downstream edge of the expanded test gas reaches the test piece; and ends at the arrival of the downstream edge of the unsteady expansion. The current X3 configuration incorporates a secondary driver which consists of an additional volume of gas (helium) between the primary diaphragm and test gas, to improve performance [7], however is not discussed here. A schematic of X3's current configuration and the evolution of flow processes is shown in Fig.…”
Section: X3 Expansion Tubementioning
confidence: 99%
“…The useful flow interval begins when the downstream edge of the expanded test gas reaches the test piece; and ends at the arrival of the downstream edge of the unsteady expansion. The current X3 configuration incorporates a secondary driver which consists of an additional volume of gas (helium) between the primary diaphragm and test gas, to improve performance [7], however is not discussed here. A schematic of X3's current configuration and the evolution of flow processes is shown in Fig.…”
Section: X3 Expansion Tubementioning
confidence: 99%
“…The facilities of interest are the X2 and X3 at the University of Queensland. Full facility descriptions can be found in [2,3]. Timescales for expansion tube flows tend to scale with characteristic length.…”
Section: Fig 1 Expansion Tube Operation and Diaphragm Fragmentation mentioning
confidence: 99%
“…This paper analyses a representative low enthalpy, X2, scramjet condition in detail, Case 2f, as documented in [2] (see Figure 2 for fill conditions). Some data is presented for the high enthalpy Case 4e.…”
Section: Fig 1 Expansion Tube Operation and Diaphragm Fragmentation mentioning
confidence: 99%
See 1 more Smart Citation
“…UQ's program aimed to establish why test flows were often noisy and unsteady, and how this [4].) 6 problem could be eliminated. They found that the key to preventing these disturbances was conducting tests in what is known as an over-tailored configuration.…”
Section: Shock Expansion Tunnelsmentioning
confidence: 99%